3D Reconstruction of the Clarified Rat Hindbrain Choroid Plexus - Perin, Paola; Rossetti, Riccardo; Ricci, Carolina; Cossellu, Daniele; Lazzarini, Simone; Bethge, Philipp; Voigt, Fabian F.; Helmchen, Fritjof; Batti, Laura; Gantar, Ivana; Pizzala, Roberto (Frontiers in Cell and Developmental Biology, 2021)
The choroid plexus (CP) acts as a regulated gate between blood and cerebrospinal fluid (CSF) . Despite its simple histology (a monostratified cuboidal epithelium overlying a vascularized stroma), there are notable differences in the arrangement of CP fronds and blood vessels between hindbrain and forebrain CPs. Our knowledge of CP vascular organization is mainly derived from resin casts; in addition, transmission electronic microscopy (TEM ) evidenced sporadic contacts of CP fronds to the brain parenchyma [Terr and Edgerton 1985]. The latter may be important, in light of CP roles in neurogenesis and neuroimmunoendocrine communication [Kaiser and Briya 2020 ]. So far, however, few studies have described CP spatial organization at the mesoscale level, because of its fragile nature and deep location within the brain. Here, using an iDISCO-based clearing approach and light-sheet microscopy [Perin et al. 2019], we have reconstructed the rat hindbrain CP macro-and microstructure, using markers for epithelium, arteries, microvasculature, and macrophages, and noted its association with 4th ventricle-related neurovascular structures. Some CP regions displayed more dispersed fronds, often terminating with “feet” touching the 4th ventricle floor (cochlear and vestibular nuclei) or cerebellum. At these points of contacts macrophages were found between CP epithelium and ependyma. Regarding vascularization, the CP receives straight arteries from the cerebellar surface, which terminate in tortuous capillaries with variable diameter and limited branching. Microvessel tortuosity follows frond geometry: within each frond a regular bidimensional network is seen. Since the medial horizontal segment (MHS) exits the ventricle at the paraflocculus level, its arterial supply is connected to the temporal bone subarcuate fossa; arterial supply for the remaining CP is instead independent of the temporal bone. This vascular arrangement makes the MHS-LHS joint particularly fragile, and very easily damaged when removing the brain from the skull. Venous outflow mostly follows arterial pathways; however, the lateral horizontal segment (LHS) drains to a ventral vein which exits through the cochlear nuclei at the Luschka foramen. We propose that this preparation is highly suitable for studying vascular connectivity and immune responses in the hindbrain CP in healthy rats and in neuroinflammatory conditions related to cerebellar and auditory/vestibular conditions..